암 환자의 정주환경을 위한 자연치유환경 블루존의 확산을 위한 정책적 방향 - 박소임(So-Im Park) (한국비교정부학보, 2024)
(Purpose) The natural healing has attracted more attention, as the effects of daily habit and surrounding environment on the maintenance of individual health has become important. On the basis of this background this study attempted to consider the direction of extended national application of the Blue Zone, a model of the healthy longevity village, from the perspective of natural healing. (Design/methodology/approach) To achieve the purpose, it conducted a case study on the wellness destination, a representative case of the Korean natural healing environment. By selection four destinations among 51 wellness destinations, it analyzed the application of factors forming the Blue Zone in such destinations, in terms of physical and operational environmental factors. (Findings) The concept of Blue Zones, focusing on sustainable health and longevity communities, requires long-term preparation and investment for its domestic introduction and systematic dissemination. In particular, strategies that promote economic activities and community reinvestment, similar to the naturally healing environments of Blue Zone areas, should be developed. This involves creating a sustainable residential revitalization model that distinguishes itself from existing initiatives such as rural revitalization, urban regeneration, and community building. These efforts need to be integrated with relevant policies, regulations, and the public sector to ensure proper organization and development. (Research implications or Originality) The results of the analysis showed some factors forming the Blue Zone, which promoting natural healing, such as application of Eco-friendly design, induction of naturally increasing gaits, social interaction based on the operation of various kinds of programs, the increase of physical activity, etc. In particular, the Korean cases were examined to show that they take strategies to actively use natural resources and infrastructures and to intensify local identity, by connecting the traditions to special products. It would be necessary to encourage residents’ economic activities and local restoration and establish the Blue Zone in which local win-win can be achieved, by promoting the natural healing environment, from the perspective of urban regeneration and local economic revitalization. KCI Citation Count: 3